In vitro study of decellularized rat tissues for nerve regeneration - Ye, Kai; He, Andong; Wu, Miaoben; Qiu, Xiaodong; Chen, Zhiwu; Yin, Jun; Song, Qinghua; Huang, Yi; Xu, Kailei; Huang, Yuye; Wei, Peng (Frontiers in Neurology, 2022)
Peripheral nerve injuries cause an absence or destruction of nerves. Decellularized nerves, acting as a replacement for autografts, have been investigated in the promotion of nerve repair and regeneration, always being incorporated with stem cells or growth factors. However, such a strategy is limited by size availability. The potential application in heterotopic transplantation of other decellularized tissues needs to be further explored. In this study, rat decellularized kidney (dK) was selected to be compared with decellularized peripheral nerve (dN), since dK has aboundant ECM components and growth factors. The PC-12 cells were cultured on dK and dN scaffolds, as shown in the similar behaviors of cell metabolism and viability, but have a more regular arrangement on dN compared to dK, indicating that the natural structure plays an important role in guiding cell extension. However, we found significant upregulation of axon–growth–associated genes and proteins of PC-12 cells in the dK group compared to the dN group by qRT-PCR, immunofluorescence, and western blotting. Furthermore, various neurotrophic factors and growth factors of acellular kidney and nerve were evaluated by ELISA assay. The lower expression of neurotrophic factors but higher expression of growth factors such as VEGF and HGF from dK suggests that axon growth and extension for PC-12 cells may be partially mediated by VEGF and HGF expression from decellularized kidney, which further points to a potential application in nerve repair and regeneration.